2012
DOI: 10.1016/j.jcf.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lung infection in patients with cystic fibrosis: Current and future strategies

Abstract: In patients with cystic fibrosis (CF) lung damage secondary to chronic infection is the main cause of death. Treatment of lung disease to reduce the impact of infection, inflammation and subsequent lung injury is therefore of major importance. Here we discuss the present status of antibiotic therapy for the major pathogens in CF airways, including prophylaxis against infection, eradication of early infection, suppression of chronic infection, and the treatment of infective exacerbations. We outline measures to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
446
1
41

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 426 publications
(499 citation statements)
references
References 165 publications
4
446
1
41
Order By: Relevance
“…Chronic P. aeruginosa infection is typically treated with chronic inhaled antibiotics to suppress infection, reduce risk of pulmonary exacerbations, improve quality of life, and preserve lung function 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic P. aeruginosa infection is typically treated with chronic inhaled antibiotics to suppress infection, reduce risk of pulmonary exacerbations, improve quality of life, and preserve lung function 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified risk factors for low FEV 1 % predicted at age 6, including female sex, poor nutritional status, viral infections, persistent infection with Pseudomonas aeruginosa (P. aeruginosa), respiratory symptoms, pulmonary exacerbations, and low socioeconomic status (3)(4)(5)(6)(7)(8). It is unclear whether these risk factors remain applicable in the current era, as children with CF born today are more likely to be detected by newborn screening (NBS) and treated more aggressively with antibiotics and CF-specific therapies, and to undergo eradication therapy when P. aeruginosa is isolated from respiratory cultures (9)(10)(11).…”
mentioning
confidence: 99%
“…Легеневі загострення обумовлюють несприятливий вплив на якість життя пацієнтів і мають вагому частку в загальній вартості медичного обслуговування [5,6].…”
Section: вступunclassified